Ants show the way Down-Under: invertebrates as bioindicators in land management - Majer, Jonathan; Andersen, A. N. (2004)
he sight of land managers poring over ant checklists is a regular occurrence in Australia, where ant monitoring has been successfully applied to a wide range of land-use situations. The robustness of ants as ecological indicators has been consistently demonstrated, and is supported by an extensive understanding of their community dynamics in relation to disturbance. Despite the widespread recognition of the value of terrestrial invertebrates as bioindicators, the use of ants represents one of the few examples where invertebrates are widely adopted in land management as indicator organisms, as opposed to being consigned to the “too hard” basket. The use of invertebrates as bioindicators in land management will always require specialist expertise and a substantial investment in resources. However, research in Australia shows that invertebrate monitoring does not require comprehensive surveys, and that it is possible to simplify sampling and processing without compromising indicator performance.